(untitled) (Economics and region, 2020)
Today, due to the sharp increase in competition, companies began to actively seek ways to radically increase business efficiency. New conditions dictate new rules of the game - improving the quality of products while reducing their cost and ensuring a quick reaction of the company to constantly changing environmental conditions. All this led to the emergence of new management approaches, among which the process approach was most developed. The requirement of flexibility and dynamism from companies can be fulfilled by managing not individual functions, but their set, which is united by the logic of their interaction. In fact, the activities of company employees consist of two types of activities: recurring (which have to be carried out periodically or in the case of certain events) and “single”, unique by the algorithm, which are not repeated in the future. The first type of activity is called processes, the second - projects, therefore, to improve the company, a project and process management system is being built. Due to the fact that the business of many companies is being built with the participation of many partners, it is now necessary not only to improve the internal processes of the company, but also to coordinate them with the internal processes of partners, which requires an in-depth understanding of the processes and the same principles for describing them in different companies. In fact, the business process has become the subject of audit, and the improvement of processes to ensure minimization of operational risks has become one of the types of improvement. Therefore, the improvement of the internal control system required not only the improvement of business processes, but also the construction of an operational risk management system in business processes and related tools. The new principle will ensure ease in changing business processes, and in fact, the tasks of designing the logic of the business process will be solved by the participants and the owner of the business process. The application of SOA-based solutions will fundamentally reduce the cost of information technology and provide mechanisms for improving business processes using information systems.